2013
DOI: 10.4028/www.scientific.net/amr.838-841.334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Numerical Methods for Piled Raft Foundations

Abstract: The methodologies used to calculate piled raft foundations are normally more complex than conventional foundations due to the large number of variables involved in the problem. In the conventional block, the interaction variables considered are only between the pile and the soil. In the piled raft, all the interaction effects must be considered, as follows: plate-soil, plate-piles and piles-soil, simultaneously. The Finite Element Method (FEM) has proven to be a useful tool in analyzing these types of problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Various studies have been conducted on the subject of defective piles. In general, however, these studies are mainly of theoretical, numerical or associated with experiments on reducedscale models studies, for example the studies of Makarchian and Poulos (199 4), Xu (2000), Novak et al (2005), Cunha et al (2010), and Freitas Neto et al (2013, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted on the subject of defective piles. In general, however, these studies are mainly of theoretical, numerical or associated with experiments on reducedscale models studies, for example the studies of Makarchian and Poulos (199 4), Xu (2000), Novak et al (2005), Cunha et al (2010), and Freitas Neto et al (2013, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Combined Pile raft foundation (CPRF) term was coined by Katzenbach et al [4] which consists of pile, raft and subsoil as the load bearing elements. After idealizing the various soil profile for combined pile raft foundation, Poulos [5,6] concluded that a uniform soil profile of relatively stiff clay or dense sand would be the favorable situations for CPRF. Analysis techniques for pile group was first developed by Butterfield and Banerjee [7] as mentioned by Randolph [8], then the analysis technique was developed for pile raft foundation by Davis and Poulos [9] and further simplified analysis methods were also developed by Hooper [10], Sommer et al [11], Franke at al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on blocks with defective piles; however, these studies are exclusively theoretical, numerical or associated with experiments on reduced-scale models. Among the most significant studies are those of Makarchian & Poulos (1994), Abdrabbo (1997), Xu (2000), Prakoso & Kulhawy (2001), Petek et al (2002), Kong & Zhang (2004), Novak et al (2005), Zhang & Wong (2007), Cordeiro (2007), Cunha et al (2007), Cunha et al (2010), Chung et al (2010), Leung et al (2010), Omeman (2012) and Freitas Neto et al (2013). Full-scale experimental studies are rare, especially those including pile defects.…”
Section: Introductionmentioning
confidence: 99%